When Mini-Publics and Maxi-Publics Coincide: Ireland's National Debate on Abortion. Issue 1 (2nd January 2023) - Farrell, David M.; Suiter, Jane; Cunningham, Kevin; Harris, Clodagh
ABSTRACT: Ireland's Citizens' Assembly (CA) of 2016–18 was tasked with making recommendations on abortion. This paper shows that from the outset its members were in large part in favour of the liberalisation of abortion (though a fair proportion were undecided), that over the course of its deliberations the CA as a whole moved in a more liberal direction on the issue, but that its position was largely reflected in the subsequent referendum vote by the population as a whole.